Rancang Bangun Sepeda Motor Listrik (SEMOLI) Generasi 3 - Nur Akhlis Sarihidaya Laksana; Bayu Aji Girawan; Radhi Ariawan; Akhlis Rahman Sari Nurhidayat (P3M Politeknik Negeri Cilacap, 2025)
In this research, the design process of the third generation of electric motorcycles (SEMOLI) is carried out, which is a development of the previous generation with the aim of developing electric vehicles using gearboxes, in order to add acceleration ratios to adjust to road or terrain conditions. as an alternative solution to the increase in fuel and the depletion of fossil energy sources. The results of this study support the national electric vehicle conversion program. The results can be used for the development of the automotive industry. The method used is research and development (R&D). The design process begins by calculating the design requirements for power transfer and frames. The frame simulation process produces a maximum stress of 149 MPa with a allowable stress of 163.2 MPa with a displacement of 2 mm. It is said to be safe to continue the manufacturing and fabrication process. The vehicle trial process produces a maximum vehicle speed of 55 km/h with an average energy consumption of 27 watts/hour.